EGO DEFENSE MECHANISM OF THE MAIN CHARACTER IN "FIGHT CLUB" NOVEL (1996) PSYCHOANALYTIC STUDY - Agus Hadi Puspito; Agnes Widyaningrum (Dinamika Bahasa dan Budaya, 2020)
This research paper analyzed the ego defense mechanism by Sigmund Freud that are found in the main character of “Fight Club“ novel. The author of novel is Chuck Palahniuk in 1996. This research applied qualitative study, and the data are derived from the novel. The researcher focuses on causes of defense mechanism, the ego defense mechanism that the main character experienced and the effect that the main character got. The researcher found that anxiety is the cause why defense mechanism of the main character can active. The main character also applied ego defense mechanism namely displacement and reaction formation. And the effect for the main character is he becomes more bravely and easier to accept the reality. The ego defense mechanism is an unconscious psychological process that helps a person overcome anxiety due to a stressful internal or external environment. The defense mechanism finds its origin in Freud's structural theory of mind, which divides the human mind into three parts: id, ego, and superego. The interaction of the ego and superego gives rise to morality, guilty, and a conscience.